A review: The nutrition components, active substances and flavonoid accumulation of Tartary buckwheat sprouts and innovative physical technology for seeds germinating - Dong, Yulu; Wang, Nan; Wang, Shunmin; Wang, Junzhen; Peng, Wenping (Frontiers in Nutrition, 2023)
Compared with the common grain, Tartary buckwheat enjoys higher nutritional value. Some distinctive nutrition associated with physiological activity of Tartary buckwheat is valuable in medicine. In addition, it’s a good feed crop. In the paper, the main components (starch, protein, amino acid, fatty acid and mineral) and polyphenol bioactive components in Tartary buckwheat and its sprouts were reviewed, and the accumulation of flavonoids in sprouts during germination, especially the methods, synthetic pathways and mechanisms of flavonoid accumulation was summarized. The research on bioactive components and health benefits of Tartary buckwheat also were reviewed. Besides, the applications of innovative physical technology including microwave, magnetic, electromagnetic, ultrasonic, and light were also mentioned and highlighted, which could promote the enrichment of some active substances during seeds germination and growth of Tartary buckwheat sprouts. It would give a good support and benefit for the research and processing of Tartary buckwheat and its sprouts in next day.